A Comparative Study of Serum Cystatin C, Serum Electrolytes, Urea and Creatinine in Early Detection of Kidney Injuries in Albino Rats Exposed to Formaldehyde (IPS Journal of Toxicology, 2021)
Aim: To ascertain early detection of possible kidney injuries in albino rats exposed to formaldehyde by assessing cystatin C, serum electrolytes, urea and creatinine. Materials/Methods: Thirty healthy adult male albino rats, weighing between 100 to 120 grams were randomly divided into three groups A, B and C. Group A served as control. Group B was exposed to low dose (100ppm of Formaldehyde), 3 hrs per day for four weeks, while group C was exposed to high Dose-200ppm of formaldehyde 3 hrs per day for four weeks. At the end of the exposure period, the rats were sacrificed by decapitation under chloroform anesthesia, and 4 ml of blood samples was collected from each rat into a plain bottle. The whole blood was allowed to clot, retracted and centrifuged at 3000 rpm for 10 minutes and serum separated. The serum was stored at -20˚C until analyses for serum electrolytes, creatinine and cystatin C. Serum electrolytes were determined using Ion selective electrode, urea and creatinine were determined using spectrophotometric methods while cystatin C was analyzed using Eliza. Data obtained was analyzed using SPSS. Results: The concentrations of the serum electrolytes, sodium. Potassium, bicarbonate and chloride were compared across the three group, they were not statistically significant (p>0.05). Urea was significantly higher in group C when compared with low dose B and control group A (P
Keywords: Formaldehyde; Kidney failure; Electrolytes; Cystatin C.